Arthropoda Diversity in High-Value Conservation Areas of Rokan Hulu's Palm Oil Ecosystems - Dewastra Bayu Wicaksana, Satya; Ardyan Pramudya Kurniawan; Prautama, Cahaya; Julia Rizki Jumas; Hutabarat, Frengky; Tambunan, Ardian Syahputra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The transformation of tropical forests into oil palm plantations in Indonesia has significantly impacted biodiversity, including arthropod species, which serve as indicators of ecosystem health. This study investigates the diversity of arthropods in High Conservation Value (HCV) areas within the oil palm ecosystem of Rokan Hulu, Riau Province. The research was conducted in three HCV areas—Sialang Forest, Makam Keramat Forest, and Pendalian River—using the Visual Encounter Survey (VES) method. Observations were made in July–August 2024, documenting species diversity and environmental parameters. A total of 187 arthropod individuals from 38 species and 12 families were identified, with Libellulidae (dragonflies) and Nymphalidae (butterflies) as the most dominant families. Diversity and evenness indices were calculated using the Shannon-Wiener and Evenness formulas, yielding values of 3.05 (high diversity) and 0.558 (moderate evenness), respectively. Environmental parameters, such as light intensity4802,00±6204,84 Lux; wind speed 0,33±0,52 m/s; humidity 72,53±16,02%; temperature 31,63±4,20°C; and soil pH 6,42±0,38 were measured, supporting arthropod distribution.